Comparison of carbetocin and oxytocin in the prevention of atonic post-partum hemorrhage following normal vaginal delivery - Anurag, Aakriti; Singh, Salomi; Kumar, Sushil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Post-partum hemorrhage is the leading cause of maternal mortality worldwide. Use of uterotonic drugs in active management of third stage of labour has been found to be most effective in prevention of PPH. Aims and objectives were to compare the efficacy and safety of carbitocin and oxytocin for prophylaxis of post-partum hemorrhage after singleton, term vaginal deliveries. Methods: Prospective randomized interventional study of 250 women with singleton term pregnancies undergoing vaginal delivery at MGM Women and Children’s Hospital, Kalamboli from May 2021 to May 2022. Participants randomized into 2 groups, group A and B receiving carbitocin and oxytocin respectively. Post-delivery uterine tone, vaginal bleeding, change in Hb and PCV, occurrence of adverse effects used to assess efficacy and safety of both drugs. Results: Carbetocin was statistically equal to oxytocin in preventing uterine atony and hence PPH, with similar duration of uterotonic action and lesser requirement of other uterotonic drugs. There was no incidence of adverse effects in either group. Conclusions: Since carbetocin is an effective, room temperature stable uterotonic drug with minimal side effects, it can be beneficial for use in prevention of PPH in rural settings.